PROTECTION OF STUDENT PRESS IN JOURNALISM: STUDENT PRESS JURNIS.ID-UNIS, TANGERANG POST-COLLABORATION BETWEEN THE PRESS COUNCIL AND THE DIRECTORATE GENERAL OF HIGHER EDUCATION - Ratna Komala; Widayat S. Noeswa (Departemen Ilmu Komunikasi Universitas Andalas, 2025)
The student press is part of the national press ecosystem, serving as a training ground for students to become journalists. The problems faced by the student press are not much different from those faced by the general press. The challenges faced by the student press include physical attacks, verbal intimidation, doxing, censorship, and even banning. The student press is more vulnerable because Law No. 40 of 1999 concerning the Press does not specifically mention campus press but only regulates legally incorporated press institutions. As a result, the position of the student press is weak; if their journalistic products are questioned, they cannot be mediated by the Press Council. It was not until 2024 that a Memorandum of Understanding (MoU) was signed by the Press Council and the Directorate General of Higher Education (DIKTI), which was opening the way for student press protection and consultation or mediation assistance with the Press Council, and training and education for campus presses as well. The research paradigm is constructivism, where truth is social reality as a social construction, and the truth of social reality is relative. In this qualitative research, we conducted in-depth observations of student press informants.